Aerobic Oxidation of Alkylaromatics using a Lipophilic N‐Hydroxyphthalimide: Overcoming the Industrial Limit of Catalyst Solubility. Issue 9 (14th July 2014) - Petroselli, Manuel; Franchi, Paola; Lucarini, Marco; Punta, Carlo; Melone, Lucio
Abstract 4, 4′‐(4, 4′‐Isopropylidenediphenoxy)bis(N‐hydroxyphthalimide), which is a new lipophilic analogue of N‐hydroxyphthalimide, can act as an effective catalyst in the aerobic oxidation of alkylaromatics under reduced amounts of polar cosolvent. The catalyst was selected on the basis of an in‐depth study of the influence that substituents on the aromatic ring of N‐hydroxyphthalimide exert on determining the NOH bond dissociation energy (BDE). BDE values for a range of model molecules are calculated by DFT and measured by EPR spectroscopy. The new catalyst can be successfully employed in the aerobic oxidation of cumene, ethylbenzene, and cyclohexylbenzene, affording, in all cases, good conversions and high selectivity for the corresponding hydroperoxide. The effect of solvent, catalyst, and temperature has also been investigated.